Depression and anxiety in juvenile systemic lupus erythematosus - kidney involvement as a specific biological signature - Beatriz Pereira Fonseca da Silva (2020)
When systemic lupus erythematosus strikes children younger than 18 years of age, it is known as Juvenile systemic lupus erythematosus (JSLE). Depression and anxiety are important aspects of lupus, but these psychological manifestations are not well understood in JSLE. To better understand the clinical and psychological factors associated with depression and anxiety in JSLE, we investigated these in a cohort of JSLE patients. The patients were compared to adult-onset SLE patients, depressed patients, and normal controls. Methods: Twenty-nine JSLE patients were recruited for the study. They were given a variety of surveys to test their psychological status and perceptions about their health, including the Hospital Anxiety and Depression scale, the Fatigue Severity Scale, and a Medical outcomes questionnaire (the SF-36). Multiple clinical lab test results were obtained from the patients' medical records. Univariate and Multivariate analyses were used to compare the patient populations and identify correlations between key physical and psychological indicators. Results: The most striking finding was that kidney disease was highly associated with depression in the JSLE patients. The BUN levels, BUN/creatinine ratio, and leukocyturia were all significantly associated with depressive symptoms. The BUN/creatinine ratio was the most predictive laboratory value for both depression and anxiety. The JSLE patients showed significantly less depression overall than the adult-onset SLE patients, although anxiety was not significantly different. There was also no significant difference between the JSLE patients and the SLE patients in the laboratory tests. JSLE patients had comparable levels of fatigue and pain to the adult-onset SLE patients. Psychosocial factors that correlated with depressive symptoms in the JSLE patients included fatigue, pain, poor general health, and inability to perform social and physical roles. The primary psychosocial factors that correlated with anxiety were decreased perception of social and emotional function. Conclusions: Kidney involvement is usually an indicator of severe lupus, and better correlated with symptoms of depression and anxiety than any other clinical measures. This may mean that symptomatology is an important indicator of whether the patient could need psychiatric care. Kidney involvement is especially important in JSLE, where it is more common than in adult-onset SLE. The JSLE patients were more anxious than depressed. The decreased overall depression among JSLE patients, despite similar clinical and psychosocial values, bears further investigation.